A Case of Competitive Aromatization vs. Sigmatropic [1,5]-Hydrogen Atom Migration in a 1,2,4-Cyclohexatriene Intermediate Derived from a Bis-Enyne Cyclization - Rong Tang; Qian Xu; Thomas R. Hoye (Molecules, 2025)
1,2,4-Cyclohexatrienes are strained, reactive intermediates often formed by the tetradehydro-Diels–Alder (TDDA) reaction of a conjugated enyne bearing a tethered alkyne as the enynophile. The ene component is commonly the π-bond of an aromatic group. In this focused study, we investigated the reactivity of a symmetrical substrate in which the pair of terminal ene moieties were simple 2-propenyl groups. The intermediate 1,2,4-cyclohexatriene, now bearing a 5-isopropenyl group, underwent competitive aromatization (the most usual outcome of the strain-relieving event of the cyclohexatriene), along with an intramolecular [1,5]-hydrogen atom migration, ultimately producing a non-benzenoid, pyrrole derivative. This represents a previously unknown process for a 1,2,4-cyclohexatriene derivative. Mechanistic aspects of the competitive processes were revealed by experiments performed in the presence of various protic additives (MeOD and BHT).